Disproportionality analysis of adverse neurological and psychiatric reactions with the ChAdOx1(Oxford-AstraZeneca) and BNT162b2 (Pfizer- BioNTech) COVID-19 vaccines in the United Kingdom - Otero Losada, Matilde (2022)
Fil: Otero Losada, Matilde. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina